Afterimage : drawing through process - Butler, Cornelia H. (Los Angeles : Museum of Contemporary Art, 1999)
Participating artists: William Anastasi, Mel Bochner, Agnes Denes, Nancy Grossman, Robert Grosvenor, Marcia Hafif, Eva Hesse, Nancy Holt, Barry Le Va, Sol LeWitt, Lee Lozano, Gordon Matta-Clark, Robert Morris, Bruce Nauman, Robert Overby, Sylvia Plimack Mangold, Yvonne Rainer, Dorothea Rockburne, Alan Saret, Joel Shapiro, Robert Smithson, Michelle Stuart, Richard Tuttle, Jack Whitten.
Published to accompany an exhibition held at the Museum of Contemporary Art, Los Angeles, Apr. 11-Aug. 22, 1999.
boek